2018
DOI: 10.1093/abm/kay065
|View full text |Cite
|
Sign up to set email alerts
|

Why does work cause fatigue? A real-time investigation of fatigue, and determinants of fatigue in nurses working 12-hour shifts

Abstract: Findings provide little support for a resource depletion model; however, the finding that control and reward both predicted fatigue is consistent with a motivational account of fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
7
32
0
Order By: Relevance
“…We also found that the utility associated with labor and leisure tasks differs between people and changes over time. Against the background that the energy metaphor (i.e., the idea that the feeling of fatigue indicates that some metaphorical mental battery is almost depleted) is increasingly being questioned (e.g., Hagger et al, 2016;Kurzban, 2016;Shenhav et al, 2017), our studies cautiously support modern views of fatigue that propose that fatigue and related phenomenology (e.g., effort, Bijleveld, 2018;boredom, Westgate & Wilson, 2018) reflect the non-energetic costs of engaging with the current activity (Hockey, 2011;Johnston et al, 2018;Kurzban, 2016;Shenhav et al, 2017). In future research, it may well be useful to continue to think of fatigue as a motivational phenomenon.…”
Section: Resultssupporting
confidence: 61%
“…We also found that the utility associated with labor and leisure tasks differs between people and changes over time. Against the background that the energy metaphor (i.e., the idea that the feeling of fatigue indicates that some metaphorical mental battery is almost depleted) is increasingly being questioned (e.g., Hagger et al, 2016;Kurzban, 2016;Shenhav et al, 2017), our studies cautiously support modern views of fatigue that propose that fatigue and related phenomenology (e.g., effort, Bijleveld, 2018;boredom, Westgate & Wilson, 2018) reflect the non-energetic costs of engaging with the current activity (Hockey, 2011;Johnston et al, 2018;Kurzban, 2016;Shenhav et al, 2017). In future research, it may well be useful to continue to think of fatigue as a motivational phenomenon.…”
Section: Resultssupporting
confidence: 61%
“…Unsurprisingly, the model once more estimates that participants half a standard deviation higher than the average in FOMO use their smartphone for 37 seconds more in 20 minutes (95% CI = [-3.38, 81.51]). The model also estimates weak evidence that the relationship between boredom and subsequent smartphone use may be stronger for those participants lower in FOMO (meanint = -33.28, 95% CI = [-75.42, 16.94]). We conclude that there is no evidence for an effect of fatigue and boredom on the amount of time the smartphone is used, provided that it is used at all.…”
Section: Fatigue Boredom and Smartphone Use At Workmentioning
confidence: 92%
“…O'Connell et al, ; Randles, Harlow, & Inzlicht, ). Moreover, aside from a recent study—which found that subjective depletion over two 12‐hour nursing shifts was not associated with perceived work demands or physical energy expended but with perceived control and reward associated with the work—studies investigating which and when individuals are more prone to ego depletion in daily life do not exist (Johnston et al, ).…”
Section: Evidence For Ego Depletion In Daily Lifementioning
confidence: 99%